LIMBAH KAYU AKIBAT PEMBUATAN JALAN HUTAN DAN TEBANG BAYANG PADA ENAM HAK PENGUSAHAAN HUTAN DI KALIMANTAN TIMUR (Wood waste caused by forest road construction and shadow cutting at six logging companies in East Kalimantan) - Maman Mansyur Idris; Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
This paper present the results of the study on logging waste caused by forest road construction and shadow cutting. The study carried out at six logging companies in East Kalimantan in 1990.The aim of the study are : (1) to determine the wood waste caused by forest road construction and shadow cutting, (2) to find the factors influencing the wood waste and (3) to find the way of reducing the wood waste.The results of this study shows that the average wood waste from trees felled caused by forest road construction and shadow cutting is 1.16 m3/ha for commercial wood species and 2. 76 m3/ha for non-commercial wood species.Keywords : wood waste, forest road, shadow cutting